Love Yourself Like Your Life Depends On It - Ravikant, Kamal (New York Harper One Publishers, 2020)
"The bestselling self-published phenomenon that sold over 300,000 copies addresses our urgent need for self-love in the world today-now expanded with new reader oriented lessons, and a powerful and transformative personal story of the practice in action"--
Keywords: Self-acceptance -- Self-esteem -- Self-actualization